Cloud services, networking, and management - Fonseca, Nelson L. S. da.; Boutaba, Raouf (Hoboken, New Jersey : John Wiley & Sons Inc., 2015)
Cloud Services, Networking and Management provides a comprehensive overview of the cloud infrastructure and services, as well as their underlying management mechanisms, including data center virtualization and networking, cloud security and reliability, big data analytics, scientific and commercial applications.
13.4 IWIR Workflow Model 314 -- 13.5 Amazon SWF Background 315 -- 13.6 RainCloud Workflow 317 -- 13.7 IWIR-to-SWF Conversion 319 -- 13.8 Experiments 324 -- 13.9 Open Challenges 328 -- 13.10 Conclusion 329 -- References 330 -- 14 INTERACTIVE MULTIMEDIA APPLICATIONS ON CLOUDS 333 -- 14.1 Introduction 333 -- 14.2 Delivery Models for Interactive Multimedia Services 335 -- 14.3 Cloud Gaming 339 -- 14.4 UGC Live Streaming 345 -- 14.5 Time-Shifting Video Streaming 351 -- 14.6 Open Challenges 353 -- 14.7 Conclusion 354 -- References 355 -- 15 BIG DATA ON CLOUDS (BDOC) 361 -- 15.1 Introduction 361 -- 15.2 Historical Perspective and State of the Art 362 -- 15.3 Clouds-Supply and Demand of Big Data 364 -- 15.4 Emerging Business Applications 365 -- 15.5 Cloud and Service Availability 368 -- 15.6 BDOC Security Issues 372 -- 15.7 BDOC Legal Issues 379 -- 15.8 Enabling Future Success-Stem Cultivation and Outreach 384 -- 15.9 Open Challenges and Future Directions 385 -- 15.10 Conclusions 388 -- References 388 -- Index 393.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Cloud computing; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Cloud computing; Electronic books; Electronic books